2005
DOI: 10.1093/qjmed/hci096
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D inadequacy among post-menopausal women: a systematic review

Abstract: The prevalence of inadequate vitamin D levels appears to be high in post-menopausal women, especially in those with osteoporosis and history of fracture. Vitamin D supplementation in this group might offer scope for prevention of falls and fracture, especially in elderly and osteoporotic populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 54 publications
6
116
0
1
Order By: Relevance
“…High calcium levels may reflect different conditions in specific groups as pHPT and low vitamin-D-levels are more common in postmenopausal [15,17] and obese women [16]. It is possible to hypothesise that calcium levels in postmenopausal and obese women may reflect PTH levels rather than vitamin-D levels and that calcium levels in premenopausal women may mainly be a marker of vitamin-D levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High calcium levels may reflect different conditions in specific groups as pHPT and low vitamin-D-levels are more common in postmenopausal [15,17] and obese women [16]. It is possible to hypothesise that calcium levels in postmenopausal and obese women may reflect PTH levels rather than vitamin-D levels and that calcium levels in premenopausal women may mainly be a marker of vitamin-D levels.…”
Section: Discussionmentioning
confidence: 99%
“…High age and obesity are associated with a high prevalence of pHPT [15,16] and low levels of vitamin-D, e.g. 25(OH)D [17]. It has also been suggested that pre-and postmenopausal women may have different risk factors for breast cancer [18] and that obesity may modify the association between established risk factors and breast cancer [19].…”
Section: Introductionmentioning
confidence: 99%
“…wearing long garments), the age, the skin pigmentation, along with a low VD dietary intake. [8][9][10] Long lactation periods, the use of skin sun blockers, the frequent use of umbrellas, 3,11,12 tobacco smoking, obesity and renal chronic disease have been also associated with VDD in women. 3,[11][12][13][14][15][16] It is not clear whether the VDD is produced by obesity or obesity is a consequence of VDD, 17 because obese individuals specially women, 18 are susceptible to VDD due to diminished availability of VD stored in the adipose tissue, and on the other hand, 18 some studies in obese individuals suggest that the supplementation with VD reduces the body fat mass.…”
Section: Vitamin D Status In Mexican Womenmentioning
confidence: 99%
“…African Americans are more prone to be deficient because of higher skin melanin levels. 70 Vitamin D inadequacy constitutes a largely unrecognized epidemic in many populations worldwide [71][72][73] It has been reported in healthy children, 74 adolescents 75 and adults. 76,77 Vitamin D and prostate health Normal and malignant prostate cells contain VDRs, [78][79][80] which mediate the antiproliferative action of 1,25(OH)2D.…”
Section: Hypovitaminosis Dmentioning
confidence: 99%